Methodical approaches to the assessment of toxicity and hazard of nanomaterials - Leonenko, N.S.; Demetska, O.V.; Leonenko, O.B. (Environment & Health, 2017)
Background: Despite the large number of test systems for screening assessment of the impact of nanoscale substances on the organism, a choice of the most sensitive ones, depending on the objectives and tasks of the study, is a high-priority task. Objective: We studied a toxicity of some nanomaterial (NM) samples by a combined indicator of the effect of general toxicity on the short-term culture of the bull’s spermatozoa and generalization of the world experience in assessment of the toxicity and hazard of nanoparticles (NPs) and NMs. Materials and methods: We investigated a cytotoxicity of nanoparticles (NPs) of metals (Mn, Co, Mg, Zn, Fe, Mo, Au) in the citrate solution. Particle sizes were measured by the analyzer «Fritch» (Germany). Toxicity assessment was performed on the AT-05 analyzer. Results: NPs of molybdenum, iron, magnesium, manganese, and cobalt didn’t show a cytotoxic effect in the native solution but gold NP demonstrated the cytotoxic effect (It, = 20.2%). In repeat study they demonstrated the cytotoxic effect in the concentrations of 5•10-3 mol/l (It, = 44.2%), 1•10-3 mol/l (It, = 68.4%) and the cytotoxic effect wasn’t detected only in the concentration of 1•10-4 mol/l (It, = 100%). In many respects this can be due to the physical-and- chemical properties of gold NPs and size which was less in comparison with other studied metals. Conclusions: Application of the alternative methods is necessary for screening assessment of the NM toxicity or nanoproducts. There is an urgent need to improve the scientific approaches to the assessment of their toxicity and hazard.